A Regulation Model for the Solvency of Banking System: Based on the Pinning Control Theory of Complex Network - Xiang Gao; Ming Zhou; Hongbing Ouyang (Discrete Dynamics in Nature and Society)
A dynamic model is proposed based on the pinning control theory of complex network in order to simulate government bailouts against financial crisis and then is applied to a stress test of China’s interbank borrowing and lending network from 2007 to 2014. The proposed model takes many cases into account, so it is able to simulate bailout effects with different parameters, capture temporal and individual differences of banks’ spillovers effects, and reflect their sensitivity to government bailouts indirectly. This paper offers an innovative model to identify the systemic-important banks in financial crisis and construct a macroprudential regulation system based on network theory.